Post-partum Mothers’ Knowledge Related to Vitamin A Consumption in Tanjung Uncang Health Center Batam City in 2021 - Yunita, Prasida; Silvia Mona (HM Publisher, 2022)
This study aims to determine the relationship between knowledge of postpartum mothers and the behavior of consuming vitamin A capsules in the working area of Tanjung Uncang Public Health Center, Batam city in 2021. This study used a cross sectional design. The research was conducted in September 2021 in the working area of the Tanjung Uncang Health Center UPT, Batam city. The sampling technique used is simple random sampling technique. Research respondents consisted of 85 mothers in the postpartum period. Most of the respondents have less knowledge (50.6%). Meanwhile, the behavior of consuming vitamin A during the puerperium was considered good (52.9%). Based on chi-square analysis, p value = 0.015 (p <0.05), so it can be concluded that there is a relationship between knowledge of postpartum mothers and behavior of consuming vitamin A capsules. In conclusion, most of the mothers during the postpartum period have less knowledge and consumption behavior. vitamin A during the good puerperium. There is a relationship between knowledge and behavior in consuming vitamin A capsules during the puerperium.